Effect of ultrasound treatment on the physicochemical and structural properties of long-chain inulin. (15th January 2022) - Lou, Xueqi; Luo, Denglin; Yue, Chonghui; Zhang, Tian; Li, Peiyan; Xu, Yunfeng; Xu, Baocheng; Xiang, Jinle
Abstract: In this study, ultrasound was employed to radiate long-chain inulin suspensions in order to obtain some new physicochemical properties. The results showed that ultrasound irradiation effectively improved the viscoelasticity of long-chain inulin samples. The samples achieved the greatest increase in the apparent viscosity and viscoelasticity after 10-min ultrasonic treatment at the intensity of 1734.9 W/cm 2 . In addition, Fourier transform infrared spectroscopy (FTIR) spectrum analysis revealed that ultrasound could not change the functional groups and molecular structure of long-chain inulin, only effect the hydrogen bonds of long-chain inulin. The results of X-ray diffraction (XRD) indicated that ultrasound also affected the relative crystallinity of long-chain inulin, depending on its intensity and treatment time. Particle size distribution indicated that long-chain inulin with particle size of 100–300 μm formed after ultrasound treatment. The changes in inulin particle size showed that inulin was unfolded by ultrasound treatment at low intensity for a short time and then aggregated with enhanced ultrasound effect. These results suggested that ultrasound treatment can change the physicochemical and structural properties of long-chain inulin, which would facilitate long-chain inulin application in the food industry. Highlights: Ultrasonic treatment improved the apparent viscosity of long-chain inulin. The G′ and G″ of long-chain inulin increased after ultrasonic treatment. Ultrasonic treatment enhanced hardness and adhesiveness of long-chain inulin. The introduction of ultrasonic changed the structure of long-chain inulin. Ultrasonic treatment changed the size of the long-chain inulin particles.